Sistem Informasi Promosi pada Toko Our Bandung Style - Pinky Octa Feroyany; Masita Ichwani Siregar; Sri Rahayu Agustiningsih; Rizda Suciyanti Restiana Dewi (Universitas Negeri Padang, 2020)
Promotional activities are needed in a business or a sales transaction to disseminate information to all consumers widely. Promotional activities will be easy to do with a web-based promotional information system that will help our Bandung Style Shop in disseminating promotional information widely. The purpose of this study is to create or design a promotional information system at Our Bandung Style Shop. The research method that we used in this research is a direct observation on the object of research so it will get more accurate. This research will produce a Web-based promotional information system design that can be used by Our Bandung Style Shop. This research was conducted by looking at the direct conditions of the object of research seen from the business processes and promotions that exist in Our Bandung Style Shop. So, the results of this study will help Our Bandung Style Shop to promote its products.